Automated citation sentiment analysis: What can we learn from biomedical researchers. Issue 1 (2013) - Yu, Bei
Abstract: Automated citation sentiment analysis is a newly emerged research topic inspired by traditional citation context analysis in scientometrics and applied linguistics. The main goals of current citation sentiment analysis are to develop new tools to model scientific literature and provide authoring support for researchers in tasks like literature review. In terms of developing authoring support tools, however, current studies have not taken into consideration the behavioral patterns of researchers' literature review practice, leaving user need assessment as a missing piece in current interdisciplinary research effort. This paper analyzed biomedical researchers' need by reviewing their publications on using manual citation sentiment analysis for detecting citation bias, and discussed the differences between biomedical researchers' approach and current automated citation sentiment analysis model. These differences are expected to inform the modeling of automated citation sentiment analysis.